Sturm und Drang in money market funds: When money market funds cease to be narrow - Stephan Jank; Michael Wedow (University of Cologne, Centre for Financial Research (CFR), 2010)
This paper investigates the returns and flows of German money market funds before and during the liquidity crisis of 2007/2008. The main findings of this paper are: in liquid times, money market funds enhanced their returns by investing in less liquid papers. By doing so they outperformed other funds as long as liquidity in the market was high. Investing in less liquid assets, however, widens the narrow structure of money market funds and makes them vulnerable to runs. During the shortening of liquidity caused by the subprime crisis, illiquid funds experienced runs, while more liquid funds functioned as a safe haven.
Keywords: G12; G20; G21; 330; Money Market Funds; Liquidity Crisis; Strategic Complementarities; Runs; Narrow Banking; Geldmarktfonds; Marktliquidität; Finanzmarktkrise; Rendite; Portfolio-Management; Deutschland